The Human Centric Aspect of Agile Maturity - Balaji, Ramkumar; Gattam, Sarath Kumar (My University, 2020)
This master thesis was conducted at the Software Installation Division(SWID) division of Case Company(CC) to investigate how individual teams have fared in terms of the human centric aspect of agile maturity. Research within agile maturity lacks exploration on factors that influence the human centric aspect of agile maturity to build on. For this research, two research questions were framed to explore and analyze the factors that contributed to the human centric aspect of agile maturity. The research question also focused on identifying opportunities for enhancing the human centric aspect of agile maturity in teams of SWID. The research methods that were used for the research include a literature review, interviews, and a survey. A literature review helped to understand the concepts of agile and agile maturity. It also supported our study by helping to identify relevant data collection methods that could be used for research. The literature review also assisted to frame questionnaires for interviews and surveys. Interviews were conducted with scrum masters from eight teams. The self-completion survey built on insight from interviews was sent out to all the members of SWID. The concept of agile maturity is intended to guide a team/organization to sustain and improve their way of working agile. For every team/organization that has undergone a recent agile transformation, agile maturity functions as a tool to track progress and identify opportunities for improvement of the agile practices. A number of factors contribute to agile maturity and in this thesis, we focused on one of the aspects namely the “Human centric”. Five factors that contributed to the human centric aspect of agile maturity were identified, namely communication, collaboration, self-organization, empowerment, and values. The value factor focuses on human values such as inclusivity and work satisfaction. The identified factors were assessed in the eight teams of SWID. Subsequently, an analysis of improvement areas for the teams in terms of communication, collaboration, self-organization, empowerment, and values was conducted. The analysis has resulted in a series of recommendations which are highlighted in the last part of the report. The authors of the thesis have put in equal efforts towards this research work.
Keywords: Agile Maturity; Agile; Human centric; Communication; Collaboration; Values; Team; Self-organization; Empowerment